COVID‐19 vaccination rates, intent, and hesitancy in patients with solid organ and blood cancers: A multicenter study. Issue 6 (18th January 2022) - Nguyen, Mike; Bain, Nathan; Grech, Lisa; Choi, Tammie; Harris, Sam; Chau, Hieu; Freeman, Daniel; Kwok, Alastair; Williams, Janne; McCartney, Amelia; Webber, Kate; Day, Daphne; et al.
Abstract: Introduction: People with cancer are at higher risk of serious illness and death from COVID‐19 infection. We investigated COVID‐19 vaccine uptake among patients with solid organ and blood cancers and explored factors related to hesitancy. Methods: Cross‐sectional online survey of adults with a history of cancer at three health services across metropolitan and regional Victoria. Vaccine hesitancy was measured by the validated Oxford COVID‐19 vaccine hesitancy scale. Results: There were 1073 respondents: 56% female; median age 62 years (range 23 ‐ 91). Commonest tumor types included breast 29%, gastrointestinal 19%, hematological 15%, genitourinary 15%, and lung 8%. Thirty‐six percent had metastatic disease, and 54% were receiving active anticancer treatment. Eighty‐four percent of respondents indicated positive intent toward COVID‐19 vaccination, 10% were undecided, and 6% indicated negative attitudes. At least one vaccine dose had been received by 65% of respondents, leaving 35% unvaccinated. Fifty‐eight percent of unvaccinated patients answered that they would "definitely" or "probably" take a vaccine. Higher vaccine uptake was significantly associated with older age, male gender, English as first language, longer time since cancer diagnosis, and not being on current anticancer treatment. Concerns regarding vaccine side effects, particularly thrombosis, and the desire for clear medical advice were prominent among unvaccinated respondents. Conclusion: Despite being eligible for COVID‐19 vaccination since March 2021, a substantial minority of patients with cancer remained unvaccinated as of August 2021. Targeted communication and educational resources addressing vaccine safety in the context of cancer are key to promoting vaccine uptake in this vulnerable population. Practitioner Points: Though achieving higher vaccination rates than the general population, a significant proportion of cancer patients remain unvaccinated despite prioritization in the vaccine rollout program. Fifty‐eight percent of unvaccinated cancer patients indicate they are "definitely" or "probably" willing to be vaccinated. Vaccine safety in the context of cancer history and treatment and lack of clear medical advice were common concerns.